A new approach for the production of a hydrogen-rich gas from biomas - an absorption enhanced reforming process (AER-GAS) - Polychronopoulou, Kyriaki; Theodorou, Zena; Costa, Costas; Efstathiou, Angelos M. (My University, 2003)
The aim of the proposed project is to convert biomass in an AER (Absorption Enhanced Reforming) process to obtain a gas containing > 80 Vol.% hydrogen with tar content < 300 mg/m3 . A CO2-absorbent in the reactor bed not only removes CO2 from the product gas but also shifts the chemical equilibrium towards H2, away from CO, hydrocarbons, soot and tar. Consequently the number of required process units is minimised, which reduces cost and increases energetic efficiency. Different catalytic absorbent materials will be investigated. The combustion of charcoal formed in AER gasification provides the heat required for the regeneration of the absorbent. Using existing gasifiers and the experience with AER hydrocarbon reforming will minimise technical risk. The produced hydrogen-rich gas can be used directly or - after gas conditioning - in fuel cells and for synfuel production.
Keywords: Biomass; Absorption enhanced reforming